Enhancement of Surfactin and Fengycin Production by Bacillus mojavensis A21: Application for Diesel Biodegradation. (10th September 2017) - Hmidet, Noomen; Ben Ayed, Hanen; Jacques, Philippe; Nasri, Moncef
Abstract : This work concerns the study of the enhancement of surfactin and fengycin production by B. mojavensis A21 and application of the produced product in diesel biodegradation. The influences of the culture medium and cells immobilization were studied. The highest lipopeptides production was achieved after 72 hours of incubation in a culture medium containing 30 g/L glucose as carbon source and a combination of yeast extract (1 g/L) and glutamic acid (5 g/L) as nitrogen sources with initial pH 7.0 at 30°C and 90% volumetric aeration. The study of primary metabolites production showed mainly the production of acetoin, with a maximum production after 24 h of strain growth. The use of immobilized cells seemed to be a promising method for improving lipopeptides productivity. In fact, the synthesis of both lipopeptides, mainly fengycin, was greatly enhanced by the immobilization of A21 cells. An increase of diesel degradation capacity of approximately 20, 27, and 40% in the presence of 0.5, 1, and 2 g/L of produced lipopeptides, respectively, was observed. Considering these properties, B. mojavensis A21 strain producing a lipopeptide mixture, containing both surfactin and fengycin, may be considered as a potential candidate for future use in bioremediation and crop protection.